SEM-EDX ANALYSIS OF ABHRAKA BHASMA PREPARED ACCORDING TO RASA RATNA SAMMUCHCHAYA - S, Vikram; Smrithi, Valsan; Bhat, *Rachana; C.V, Sruthi; Amrutha, Sahni (International Journal of Ayurveda and Pharma Research, 2019)
Bhasmas are the most frequently used medicines in the field of Ayurveda as it tends to act fast when compared to other modes of medication. It works on the principle of nanoparticle assimilation, which provides higher bioavailability due its higher surface area and lesser particle size. This invention was made back in ancient days, which proves that during those ages there were faster methods of medical aids for a disease proving to be fatal. Abhraka is one of the main drugs used in Ayurveda mainly in the form of a Bhasma. It is abundantly used in single / compound forms for diseases like Cold, Cough, Diabetes, Anemia, asthma, etc. For a Bhasma to act significantly without side-effects it has to be properly rendered to purifactory procedures and Incineration at optimum temperature. This article basically deals with Samanya Shodana, Dhanyabhraka nirmana and Marana of Abhraka followed by its analysis by SEM-EDX which proved that There was reduction in some of the elements present in the drug after giving successive putas, till the formation of a Bhasma.The atomic percentage of Oxygen increased when bhasma was formed, hence suggesting it to be in oxide form. There was absence of heavy metals after giving puta according to the classical reference. Microscopic images of the Churna and Bhasma could be analysed and the Particle size of bhasma could be analysed which was 580.2 nm.